1995
DOI: 10.1097/00005373-199505000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia and Specific Antibody Behavior against Different Endotoxins following Multiple Injuries

Abstract: The aim of this study was to establish the incidence of endotoxemia and the influence of endotoxin on specific antibody response after multiple injury. Blood samples were collected from 39 patients (median Injury Severity Score: 20.5) at 0-3 and 6-12 hours, and 1, 3, 5, and 10 days after admission. The endotoxin plasma levels were high at the first time point (mean = 0.421 endotoxin units/mL) and decreased in the later course. Total immunoglobulin levels of IgM, IgG, or IgA were low and increased throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…The translocated lipopolysaccharide (LPS) from the gut (Hiki et al, 1995;Buttenschoen et al, 2000) has been indicated to potently trigger the inflammatory response to trauma, including bone fracture (Tobias et al, 1997); it has also been identified as a major bacterial deregulator in the activity imbalance of osteoblasts and osteoclasts (Nair et al, 1996). Thus, the effect of LPS on bone metabolism is therefore conceived to pose a clinical challenge to bone healing, particularly for trauma followed by endotoxinemia/sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The translocated lipopolysaccharide (LPS) from the gut (Hiki et al, 1995;Buttenschoen et al, 2000) has been indicated to potently trigger the inflammatory response to trauma, including bone fracture (Tobias et al, 1997); it has also been identified as a major bacterial deregulator in the activity imbalance of osteoblasts and osteoclasts (Nair et al, 1996). Thus, the effect of LPS on bone metabolism is therefore conceived to pose a clinical challenge to bone healing, particularly for trauma followed by endotoxinemia/sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed significant endotoxemia after cardiac and general surgical procedures and after multiple injury [22][23][24][25][26][27][28]. The origin of the endotoxin reaching the cir culation was presumed to be the gastrointesti nal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is a likely feature of bone repair processes, and several cytokines have been reported to be involved in bone metabolism (Girasole et al 1994, Einhorn et al 1995, Lader and Flanagan 1998, Ueda et al 1998, Ohlin et al 1999, Suda et al 1999. Experimental and clinical experience indicates that trauma causes translocation of lipopolysaccharide (LPS) endotoxin from the gut (Hiki et al 1995, Buttenschoen et al 2000. LPS is a potent trigger of the mediator cascade and the inflammatory response (Tobia et al 1997), and it has been identified as a major bacterial bone resorbing factor (Nair et al 1996).…”
mentioning
confidence: 99%